R-Loop Formation in Meiosis: Roles in Meiotic Transcription-Associated DNA Damage - Yasuhiro Fujiwara; Mary Ann Handel; Yuki Okada (Epigenomes, 2022)
Meiosis is specialized cell division during gametogenesis that produces genetically unique gametes via homologous recombination. Meiotic homologous recombination entails repairing programmed 200–300 DNA double-strand breaks generated during the early prophase. To avoid interference between meiotic gene transcription and homologous recombination, mammalian meiosis is thought to employ a strategy of exclusively transcribing meiotic or post-meiotic genes before their use. Recent studies have shown that R-loops, three-stranded DNA/RNA hybrid nucleotide structures formed during transcription, play a crucial role in transcription and genome integrity. Although our knowledge about the function of R-loops during meiosis is limited, recent findings in mouse models have suggested that they play crucial roles in meiosis. Given that defective formation of an R-loop can cause abnormal transcription and transcription-coupled DNA damage, the precise regulatory network of R-loops may be essential in vivo for the faithful progression of mammalian meiosis and gametogenesis.